URGENSI PEMBENTUKAN PERATURAN DAERAH PARTISIPATIF DI KABUPATEN NABIRE - Petrus Tekege (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The purpose of this study are: (1). To find the level of problems of the Implementation of Law No. 21 of 2001 concerning Special Autonomy for the Papua Province towards increasing community welfare in Kampung Bumi Mulia District of Nabire District Wanggar. (2). Providing solutions to problem solving to the government through research seminar results, and published through journals. Thus the specific target expected to be achieved from the results of this study is the creation of a maximum Government Service for Increasing Welfare by implementing Law Number 21 Year 2001 concerning Special Autonomy for the Papua Province so that the welfare of the Papuan people in Kampung Bumi Mulia increases according to the purpose of Invite the Special Autonomy.